INFLUENCE OF EMOTIONAL INTELLEGENCE AND WORK ENVIROMENT PHYSICAL ON PERFORMANCE OF REST AREA EMPLOYEES - Diana Aprillia Zulva; Alex Winarno (Jurnal Education and Development, 2021)
The competition in the rest area service business is currently very competitive. Companies engaged in the service sector are required to always improve their effectiveness through improving the performance of their employees. Employee performance can reflect the company's performance. This study aims to provide an analysis of the influence of emotional intelligence and physical work environment on the level of employee performance at the km 57 rest area company. The study was conducted in companies operating in the service sector of the KM 57 rest area of the Jakarta Cikampek Toll Road which is the busiest toll road in Indonesia. . One of the main services in the rest area business is the sale of motor vehicle fuel. Changes in operating equipment technology used to distribute vehicle fuel encourage companies to increase the competence of equipment operator employees. Appropriate emotional intelligence and a good work environment will be important aspects related to employee performance. The method of data collection is done by saturated sampling technique. The number of samples is 40 permanent employees of PT Mitra Buana Jaya Lestari, a rest area operator company KM 57. The data were analyzed using descriptive analysis and multiple linear regression, with the help of the SPSS version of the application 25. The results show that emotional intelligence and physical work environment affect employee performance either partially or simultaneously.